Corpora and Language Learning: Ways to Use Corpora in Classroom - Alif Ilham Baiquni (Universitas Negeri Yogyakarta, 2022)
Corpus-based studies usually involve the comparison of two corpora, in which translated texts are compared with either their source texts or with another corpus constructed according to similar design criteria, either in the same or in another language. The ability of using corpora for language teaching has been questioned from different perspectives. The skeptics have expressed reservations about the ability of corpora to capture language use in providing a model for teaching. However, due to corpus linguistics is based on the theory that language varies according to context, its potential for finding out new facts about language is infinite. This includes designing them for teaching and learning in the classroom which can be applied indirectly and directly. In this paper, the writer proposes ways of using corpora in the classroom by considering how best corpora can aid language learning and teaching and how to deal with the theoretical and practical implications of the body of work dealing with corpora in the classroom.Keywords: corpora, language learning, classroom.